The impact of commercial peer-to-peer lending websites on the finance of small business ventures - Kgoroeadira, Reabetswe (Cranfield University, 2014)
In this dissertation, we set out to examine empirically the impact of commercial Peer to Peer (P2P) lending on the finance of small business ventures. Since, this is the first study that looks at the funding of small business ventures by commercial P2P lending website; we have collected and created a new and unique data set taken from Prosper.com, one of the dominating P2P lending websites; which formed the basis of our analysis. These data offer a unique opportunity to test theory - looking at information asymmetry problems and the mechanisms adopted to deal with them within a new context. The thesis comprises of three empirical chapters; we follow entrepreneurial finance literature in raising some of the key questions concerned mainly with: credit extension, the cost of credit and modeling default. We use robust analysis methods specifically: Probit, Tobit and 2-stage Heckman models to check for factors that drive credit allocation, factors driving the cost of credit and determinants driving default for small business loans. General insights from our first empirical study shows that P2P lending depicts a new small business venture loan market, where previously underserved early stage entrepreneurs and those looking for small amounts are able to access unsecured credit through the relaxation of collateral. Although collateral is not required, we find that the supply of loans tends to flow to the least risky entrepreneurs; those who are homeowners, with high credit ratings. In our findings, we also demonstrate that firm level characteristics have little impact on loan supply while reducing information asymmetries through giving volunteering information improves access to loans. In general, our findings are both interesting and important as they suggest that P2P lending is a low risk form of debt finance. In this sense, lenders act like traditional debt financiers. However, the way in which they appraise funding opportunities characterise typical decision making of equity investors such as Business Angels and VC, who tend to focus more on people, rather than the business itself. Findings from the second empirical study suggest that at an average lending of between 18 percent and 20 percent; P2P lending is a very expensive form of debt finance. Banks typically refuse to extend credit given such high interest rates as this tends to alter the borrower pool such that only the riskiest of borrowers have projects that generate returns that are high enough to be able to re-pay these interest rates. In effect, the bank supply curve is backward bending above 10 percent on conventional terms of lending. Consequently, if we were to characterise P2P lending we would effectively conclude that it is typically a high cost finance with required returns expected to be likely in the levels of Business Angels and VC equity investments. Finally, In terms of lender return and default, we find that the expected return to lenders is 3.26 percent, which is above the opportunity cost of capital in the US. Therefore, P2P lending is profitable from the investor point of view, albeit in a narrow sense. In general, the results suggest that average lenders on P2P platforms are amateurs, who actually have a higher risk tolerance. For these lenders, the risk of losing a small proportion (as little as $25) per investment in the overall portfolio of loans is offset by the potential gain from high interest rates charged for loans. Interestingly, our results show that return from the top 5 percent of lenders average at 6.1 percent per annum. Given the fact that P2P lending is generally a young market, and the fact that majority of lenders attracted to P2P lending are relatively uninformed amateurs in making investment decisions, the results suggest that if the amateur lenders do indeed learn, it then becomes plausible that in time the returns in this market may generally converge to be better (and gravitate towards the 6.1 percent achieved by top 5 percent). However, if the P2P lending platforms continue to attract a pool of amateur lenders, the average returns of 3.26 percent may render the market somewhat unsustainable in the long run. Overall, our findings are novel, namely that P2P lending depicts a new venture loan market where previously underserved early stage ventures and those looking for small amounts are able to access credit; with the relaxation of typical collateral requirements. The big lesson however about P2P lending as a form of small business finance is that it really comes down to personal features rather than business features. Put another way, our findings suggests that the decision to extend credit and the pricing of loans in this context may possibly be relatively idiosyncratic - depending more on personal reputation of the small business owner than on the observed characteristics of the firm.